A composite anti-wear coating combined structured grinding wheel and preparation method thereof

By designing the bird feather-like microstructure arranged in leaf sequence on the surface of the grinding wheel and preparing the MoS2-TiAlN composite anti-wear coating, the problems of thermal damage and low utilization rate of grinding fluid during high-speed grinding are solved, and more efficient grinding and longer grinding wheel life are achieved.

CN118422122BActive Publication Date: 2025-04-25SHANTOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410745649.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-11
Publication Date
2025-04-25
Estimated Expiration
2044-06-11

AI Technical Summary

Technical Problem

During high-speed grinding, heat and chips cannot be discharged in time, resulting in thermal damage to the surface of the processed workpiece, affecting the grinding accuracy and tool life. At the same time, grinding fluid is difficult to enter the working area, resulting in unsatisfactory processing accuracy and a large amount of waste liquids that are harmful to the human body and the environment.

Method used

A composite anti-wear coating combined structured grinding wheel is designed with a bird feather-like microstructure arranged in leaf order on the surface, and the MoS2-TiAlN composite anti-wear coating is re-transmitted on the Ti transition layer, and prepared by bionic microstructured processing and radio frequency magnetron sputtering.

Benefits of technology

It improves the utilization rate of grinding fluid, reduces the loss of grinding fluid, reduces grinding temperature and wear, extends the service life of the grinding wheel, and improves grinding efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118422122B_ABST
    Figure CN118422122B_ABST
Patent Text Reader

Abstract

The present invention provides a composite anti-wear coating combined structured grinding wheel and a preparation method thereof, the method comprising: firstly performing bionic microstructuring processing on the surface of the grinding wheel substrate to form a phyllose-arranged bird-feather-like microstructure, and then performing surface treatment on the grinding wheel substrate; then preparing a Ti transition layer on the substrate; and finally applying a layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer. The method of the present invention adopts a phyllose-arranged bionic bird-feather structure, which can improve the chip removal ability, prevent broken abrasive particles and debris from clogging the grinding wheel, and can effectively store the grinding fluid, improve the effective utilization rate of the grinding fluid, thereby reducing the grinding temperature and wear. At the same time, after being coated with the MoS2+TiAlN coating, the grinding wheel has the advantages of high hardness, wear resistance, corrosion resistance, high melting point and high thermal conductivity, which improves the hardness, strength, wear resistance and oxidation resistance of the grinding wheel, thereby extending the service life of the grinding wheel and improving the grinding efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grinding wheel finishing, in particular to a composite anti-wear coating combined structured grinding wheel and a preparation method thereof. Background Art

[0002] With the advancement of manufacturing technology in my country, the demand for processing various difficult-to-process materials (such as high-silicon aluminum materials, high-wear-resistant materials, etc.) continues to increase. Diamond wheel grinding, as the main processing method for engineering ceramics, has attracted much attention in recent years. Compared with other processing methods, diamond wheel grinding has significant advantages such as high strength, long life, high surface quality, high precision, and high efficiency.

[0003] However, during high-speed grinding, heat and chips cannot be discharged in time, which will cause thermal damage to the workpiece surface, affecting grinding accuracy and tool life. Using grinding fluid is a way to reduce heat generation. However, it is difficult for grinding fluid to enter the working area, resulting in unsatisfactory machining accuracy, and a large amount of waste liquid that is harmful to the human body and the environment is generated in the process. Summary of the invention

[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a composite anti-wear coating combined structured grinding wheel and a preparation method thereof. Starting from the structure of the grinding wheel, the present invention incorporates the fluid dynamic characteristics of bird feathers and phyllotaxis into the design to manufacture a grinding wheel with a combined bionic surface structure. This new design helps to improve the utilization rate of the grinding fluid, reduce pollution to the environment, and provide a new research direction for green processing.

[0005] To achieve the above object, the present invention provides a method for preparing a composite anti-wear coating combined structured grinding wheel, comprising the following steps:

[0006] Step 1: Performing bionic microstructuring processing on the surface of the grinding wheel substrate to form a bird-feather-like microstructure arranged in leaf sequence on the surface of the grinding wheel;

[0007] Step 2, performing surface treatment on the grinding wheel substrate processed by the bionic microstructuring in step 1;

[0008] Step 3, preparing a Ti transition layer on the grinding wheel substrate after surface treatment;

[0009] Step 4: adopt a dual-target radio frequency magnetron sputtering method, using MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3, so as to obtain the composite anti-wear coating combined structured grinding wheel.

[0010] Furthermore, in step one, a femtosecond laser is used to perform bionic microstructuring processing on the surface of the grinding wheel, specifically: first, the bird feather structure is drawn into a pattern according to the leaf sequence; then, the drawn pattern is imported into the laser system, and by setting relevant parameters of the laser processing, the system scans and ablates the grinding wheel surface along the pattern traces; finally, bird feather grooves arranged according to the leaf sequence are formed on the surface of the grinding wheel.

[0011] Furthermore, in step 1, the average power of the laser used is 1-50w, the repetition frequency is 1-80Mhz, the pulse width is 120fs, the wavelength is 720-1060nm, and the laser spot diameter is within 10um.

[0012] Furthermore, in step 1, the number of the phyllotaxy-sorted abrasive clusters is 250-400, and the phyllotaxy coefficient is 0.2-0.6.

[0013] Furthermore, the shape of the bionic microstructure is a bionic bird feather, and the specific structural parameters are: groove depth is 0.2-0.4mm, axis groove width is 0.8-1.2mm, barb groove width is 0.4-0.6mm, the distance between two barb grooves is 1.4-1.6mm, the barb groove angle is 30°-45°, and the number of barbs is 4-6.

[0014] Furthermore, in step 2, the grinding wheel substrate after the bionic microstructuring processing in step 1 is surface treated, specifically: first, the grinding wheel is cleaned with clean water, then the substrate is placed in a sodium hydroxide solution, then the substrate is placed in a nitric acid solution, and finally the substrate is dried.

[0015] Furthermore, in step four, the preparation of the MoS2-TiAlN composite anti-wear coating is specifically as follows: first, select suitable MoS2 target materials and TiAlN target materials; second, place the cleaned substrate and target materials in an ion plating machine, and evacuate the working room to a vacuum state; then introduce Ar gas to maintain the gas pressure at 2-5Pa; finally, use ions to bombard the target materials to ionize the atoms on the surfaces of the MoS2 target materials and the TiAlN target materials and deposit them on the substrate surface to form a composite anti-wear coating.

[0016] Furthermore, the purity of the MoS2 target and the TiAlN target are both 99.99%, the sputtering time is 1-2 h, the working gas pressure is maintained at 5 Pa, and the content of MoS2 and TiAlN in the coating is controlled to be 6:1 by adjusting the RF power supply current.

[0017] Furthermore, the thickness of the Ti transition layer is 0.3-0.5um; the thickness of the MoS2+TiAlN composite anti-wear coating is 1-1.2um.

[0018] The present invention also provides a composite anti-wear coating combined structured grinding wheel, which is prepared by the above-mentioned preparation method; the grinding wheel includes a grinding wheel substrate, and the surface of the grinding wheel substrate is provided with a phylloses arranged bird feather-like microstructure; the surface of the grinding wheel substrate is provided with a Ti transition layer and a MoS2-TiAlN composite anti-wear coating in sequence.

[0019] The present invention has the following beneficial effects:

[0020] 1. The present invention provides a method for preparing a composite anti-wear coating combined structured grinding wheel, which adopts a bionic microstructure of leaf sequence sorting + bird feather combination, and has the characteristics of guiding the airflow to flow evenly, thereby achieving the purpose of improving the utilization rate of grinding fluid and reducing the loss of grinding fluid. In addition, the microstructuring of the grinding wheel surface can improve the chip removal ability, prevent broken abrasive particles and debris from clogging the grinding wheel, and can effectively store the grinding fluid, improve the effective utilization rate of the grinding fluid, thereby reducing the grinding temperature and wear. The feather-shaped grooves used in the present invention can reduce the number of cutting edges in instantaneous contact in the grinding area, thereby reducing the number of abrasive particles in the scraping process and reducing the grinding force.

[0021] 2. In the preparation method of a composite anti-wear coating combined structured grinding wheel provided by the present invention, a MoS2-TiAlN composite anti-wear coating is provided. Due to the addition of Al element, the grinding wheel has the advantages of high hardness, wear resistance, corrosion resistance, high melting point and high thermal conductivity. At high temperature, Al ions will diffuse to the surface and easily form a dense Al2O3 protective film, which improves the hardness, strength, wear resistance and oxidation resistance of the grinding wheel, thereby extending the service life of the grinding wheel and improving the grinding efficiency. The Ti transition layer deposition treatment is first performed on the grinding wheel substrate, which serves to improve the adhesion between the diamond grinding wheel substrate and the molybdenum disulfide coating and improve the quality of the molybdenum disulfide coating.

[0022] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0024] Figure 1 It is a processing flow chart of the present invention;

[0025] Figure 2 is a schematic diagram of the microstructure surface of the present invention;

[0026] Figure 3 This is a schematic diagram of the principle of preparing MoS2+TiAlN composite coating by radio frequency magnetron sputtering method of the present invention;

[0027] Figure 4 Schematic diagram of the grinding wheel coating of the present invention. DETAILED DESCRIPTION

[0028] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0029] As attached Figure 1 As shown, a method for preparing a composite anti-wear coating combined structured grinding wheel comprises the following steps:

[0030] Step 1: Performing bionic microstructuring on the surface of the grinding wheel to form a bird-feather-like microstructure arranged in leaf sequence on the surface of the grinding wheel;

[0031] Step 2, performing surface treatment on the grinding wheel substrate of step 1;

[0032] Step 3, preparing a Ti transition layer on the grinding wheel substrate after surface treatment;

[0033] Step 4: adopt a dual-target radio frequency magnetron sputtering method, using MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3, so as to obtain the composite anti-wear coating combined structured grinding wheel.

[0034] In step one, a femtosecond laser is used to perform bionic microstructuring on the surface of the diamond grinding wheel. First, the bird feather structure is drawn into a pattern according to the phyllotaxis. Then, the drawn pattern is imported into the laser system, and by setting the laser processing spot size, processing time and other related parameters, the system scans and ablates the grinding wheel surface along the pattern traces. Finally, bird feather grooves arranged in phyllotaxis are formed. The average power of the laser used is 1-50w, the repetition frequency is 1-80Mhz, the pulse width is 120fs, the wavelength is 720-1060nm, and the laser spot diameter is within 10um. The number of abrasive clusters in the phyllotaxis is 250-400, and the phyllotaxis coefficient is 0.2-0.6. The shape of the bionic microstructure is a bionic bird feather, and the specific structural parameters are: groove depth is 0.2-0.4mm, axis groove width is 0.8-1.2mm, barb groove width is 0.4-0.6mm, the distance between two barb grooves is 1.4-1.6mm, the barb groove angle is 30°-45°, and the number of barbs is 4-6.

[0035] The surface of the diamond grinding wheel is microstructured using laser processing technology. Due to the surface structure effect, the airflow on the grinding wheel surface is uniform, thereby achieving the purpose of improving the utilization rate of the grinding fluid and reducing the loss of the grinding fluid. In addition, the microstructuring of the grinding wheel surface can improve the chip removal ability, prevent broken abrasive particles and debris from clogging the grinding wheel, and can effectively store the grinding fluid, improve the effective utilization rate of the grinding fluid, thereby reducing the grinding temperature and wear. Figure 2 Schematic diagram of a diamond grinding wheel. The feather-shaped grooves used in the present invention can reduce the number of cutting edges in instantaneous contact in the grinding zone, thereby reducing the number of abrasive particles during the scraping process and reducing the grinding force.

[0036] In step 2, clean water is used to clean the diamond grinding wheel to remove most of the impurities on the surface of the substrate. Then the substrate is placed in a sodium hydroxide solution to remove the grease on the surface of the substrate. Then the substrate is placed in a nitric acid solution to remove the surface oxide. Finally, the substrate is dried.

[0037] In step 3, a plasma cleaning machine is used to perform glow cleaning on the substrate to remove dirt and impurities on the substrate surface; then, a DC magnetron power supply is turned on to prepare a Ti transition layer on the substrate. The Ti transition layer deposition treatment is performed on the diamond grinding wheel substrate to improve the adhesion between the diamond grinding wheel substrate and the molybdenum disulfide coating and improve the quality of the molybdenum disulfide coating.

[0038] In step 4, a composite anti-wear coating is prepared by using a dual-target radio frequency magnetron sputtering method and a composite multifunctional ion plating machine, using MoS2 target and TiAlN target. The thickness of the composite anti-wear coating is 1-1.2 um.

[0039] The radio frequency magnetron sputtering method for making molybdenum disulfide and aluminum titanium nitride thin films has low technical costs, fast deposition speed, low substrate temperature rise, and little damage to the film layer. The composite film obtained by sputtering is well bonded to the substrate. The bionic structure will cause a certain degree of wear on the molybdenum disulfide coating, and it is easy for the coating abrasive particles of the diamond grinding wheel to fall off during high-temperature processing. The aluminum titanium nitride coating has the advantages of high hardness, wear resistance, corrosion resistance, high temperature resistance, and good thermal conductivity. After coating, the grinding wheel has higher hardness, strength, and wear resistance, which increases the service life and grinding efficiency of the grinding wheel. As shown in the attached Figure 3 Schematic diagram of the principle of preparing TiAlN coating by radio frequency magnetron sputtering.

[0040] The steps for preparing the MoS2-TiAlN composite coating are as follows: First, select a suitable MoS2 target and a TiAlN target. Second, place the cleaned substrate and target in an ion plating machine and evacuate the working chamber. Then introduce Ar gas and maintain the pressure at 5 Pa to make the atoms on the surface of the target more active. Finally, bombard the target with ions to ionize the atoms on the surface of the MoS2 target and the TiAlN target and deposit them on the substrate surface to form a composite coating. Finally, the attached Figure 4 Schematic diagram of grinding wheel coating.

[0041] The present invention is explained below with reference to specific embodiments.

[0042] Embodiment 1:

[0043] A method for preparing a composite anti-wear coating combined structured grinding wheel comprises the following steps:

[0044] Step 1: Perform bionic microstructuring on the surface of the grinding wheel to form a bird-feather-like microstructure with phyllotaxy arrangement on the surface of the grinding wheel.

[0045] Specifically, a femtosecond laser is used to perform bionic microstructuring on the surface of a diamond grinding wheel. First, the bird feather structure is drawn into a pattern according to the leaf sequence. Then, the drawn pattern is imported into the laser system, and by setting the laser processing spot size, processing time and other related parameters, the system scans and ablates the grinding wheel surface along the pattern traces. Finally, bird feather grooves arranged according to the leaf sequence are formed.

[0046] The average power of the laser used in this embodiment is 5w, the repetition frequency is 80Mhz, the pulse width is 120fs, and the wavelength is 870nm. The diameter of the laser spot is within 10um, and a bird feather structure is processed along the arc on the surface of the grinding wheel. The number of abrasive clusters in leaf sequence is 330, and the leaf sequence coefficient is 0.4865. The bird feather structure parameters are groove depth of 0.3mm, shaft groove width of 1mm, barb groove width of 0.5mm, distance between two barb grooves of 1.5mm, barb groove angle of 35°, and number of barbs of 6. As shown in the attached figure Figure 2 shown.

[0047] Step 2: Surface treatment of the grinding wheel substrate in step 1. Specifically: first use clean water to clean the diamond grinding wheel to remove most of the impurities on the substrate surface. Then put the substrate into a sodium hydroxide solution to remove the grease on the substrate surface. Then put the substrate into a nitric acid solution to remove the surface oxide. Finally, dry the substrate.

[0048] Step 3: Use a plasma cleaning machine to perform glow cleaning on the substrate to remove dirt and impurities on the surface of the substrate; then, turn on the DC magnetron power supply to prepare a Ti transition layer on the surface-treated grinding wheel substrate.

[0049] Step 4, adopt the dual-target radio frequency magnetron sputtering method, use MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3. Specifically: First, select suitable MoS2 target material and TiAlN target material. Secondly, place the cleaned substrate and target material in an ion plating machine, and evacuate the studio to a vacuum state. Then introduce Ar gas and maintain the air pressure at 5Pa to make the atoms on the surface of the target material more active. Finally, use ions to bombard the target material to ionize the atoms on the surface of the MoS2 target material and the TiAlN target material and deposit them on the surface of the substrate to obtain the composite anti-wear coating combined structured grinding wheel.

[0050] Embodiment 2:

[0051] A method for preparing a composite anti-wear coating combined structured grinding wheel comprises the following steps:

[0052] Step 1: Perform bionic microstructuring on the surface of the grinding wheel to form a bird-feather-like microstructure with phyllotaxy arrangement on the surface of the grinding wheel.

[0053] Specifically, a femtosecond laser is used to perform bionic microstructuring on the surface of a diamond grinding wheel. First, the bird feather structure is drawn into a pattern according to the leaf sequence. Then, the drawn pattern is imported into the laser system, and by setting the laser processing spot size, processing time and other related parameters, the system scans and ablates the grinding wheel surface along the pattern traces. Finally, bird feather grooves arranged according to the leaf sequence are formed.

[0054] The average power of the laser used in this embodiment is 5w, the repetition frequency is 80Mhz, the pulse width is 120fs, and the wavelength is 870nm. The laser spot diameter is within 10um, and the bird feather structure is processed along the arc on the surface of the grinding wheel. The number of abrasive clusters in leaf sequence is 250, and the leaf sequence coefficient is 0.2. The bird feather structure parameters are groove depth of 0.2mm, shaft groove width of 0.8mm, barb groove width of 0.4mm, distance between two barb grooves of 1.4mm, barb groove angle of 30°, and number of barbs of 4.

[0055] Step 2: Surface treatment of the grinding wheel substrate in step 1. Specifically: first use clean water to clean the diamond grinding wheel to remove most of the impurities on the substrate surface. Then put the substrate into a sodium hydroxide solution to remove the grease on the substrate surface. Then put the substrate into a nitric acid solution to remove the surface oxide. Finally, dry the substrate.

[0056] Step 3: Use a plasma cleaning machine to perform glow cleaning on the substrate to remove dirt and impurities on the surface of the substrate; then, turn on the DC magnetron power supply to prepare a Ti transition layer on the surface-treated grinding wheel substrate.

[0057] Step 4, adopt the dual-target radio frequency magnetron sputtering method, use MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3. Specifically: First, select suitable MoS2 target material and TiAlN target material. Secondly, place the cleaned substrate and target material in an ion plating machine, and evacuate the studio to a vacuum state. Then introduce Ar gas and maintain the air pressure at 5Pa to make the atoms on the surface of the target material more active. Finally, use ions to bombard the target material to ionize the atoms on the surface of the MoS2 target material and the TiAlN target material and deposit them on the surface of the substrate to obtain the composite anti-wear coating combined structured grinding wheel.

[0058] Embodiment 3:

[0059] A method for preparing a composite anti-wear coating combined structured grinding wheel comprises the following steps:

[0060] Step 1: Perform bionic microstructuring on the surface of the grinding wheel to form a bird-feather-like microstructure with phyllotaxy arrangement on the surface of the grinding wheel.

[0061] Specifically, a femtosecond laser is used to perform bionic microstructuring on the surface of a diamond grinding wheel. First, the bird feather structure is drawn into a pattern according to the leaf sequence. Then, the drawn pattern is imported into the laser system, and by setting the laser processing spot size, processing time and other related parameters, the system scans and ablates the grinding wheel surface along the pattern traces. Finally, bird feather grooves arranged according to the leaf sequence are formed.

[0062] The average power of the laser used in this embodiment is 5w, the repetition frequency is 80Mhz, the pulse width is 120fs, and the wavelength is 870nm. The laser spot diameter is within 10um, and the bird feather structure is processed along the arc on the surface of the grinding wheel. The number of abrasive clusters in leaf sequence is 400, and the leaf sequence coefficient is 0.6. The bird feather structure parameters are groove depth of 0.4mm, shaft groove width of 1.2mm, barb groove width of 0.6mm, distance between two barb grooves of 1.6mm, barb groove angle of 45°, and number of barbs of 5.

[0063] Step 2: Surface treatment of the grinding wheel substrate in step 1. Specifically: first use clean water to clean the diamond grinding wheel to remove most of the impurities on the substrate surface. Then put the substrate into a sodium hydroxide solution to remove the grease on the substrate surface. Then put the substrate into a nitric acid solution to remove the surface oxide. Finally, dry the substrate.

[0064] Step 3: Use a plasma cleaning machine to perform glow cleaning on the substrate to remove dirt and impurities on the surface of the substrate; then, turn on the DC magnetron power supply to prepare a Ti transition layer on the surface-treated grinding wheel substrate.

[0065] Step 4, adopt the dual-target radio frequency magnetron sputtering method, use MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3. Specifically: First, select suitable MoS2 target material and TiAlN target material. Secondly, place the cleaned substrate and target material in an ion plating machine, and evacuate the studio to a vacuum state. Then introduce Ar gas and maintain the air pressure at 5Pa to make the atoms on the surface of the target material more active. Finally, use ions to bombard the target material to ionize the atoms on the surface of the MoS2 target material and the TiAlN target material and deposit them on the surface of the substrate to obtain the composite anti-wear coating combined structured grinding wheel.

[0066] Comparative Example 1: (No phyllotaxy arranged bird-feather-like microstructure)

[0067] The difference between Comparative Example 1 and Example 1 is that: there is no step 1 in which the surface of the grinding wheel is subjected to bionic microstructuring processing; the other steps are the same as those of Example 1.

[0068] Comparative Example 2: (without MoS2-TiAlN composite anti-wear coating)

[0069] The difference between Comparative Example 2 and Example 1 is that: there is no step 4 of preparing the MoS2+TiAlN composite anti-wear coating; the other steps are the same as Example 1.

[0070] The performance of the grinding wheel substrates treated by Example 1 and Comparative Examples 1-2 was tested, and the test results are shown in Tables 1 and 2.

[0071] Table 1

[0072]

[0073] Table 2

[0074]

[0075] It can be seen from Table 1 and Table 2 that the composite anti-wear coating combined structured grinding wheel prepared by the method of the present invention is superior to Comparative Example 1 and Comparative Example 2 in terms of performance. In particular, when the cutting depth is 20um, the effective grinding fluid of Example 1 of the present invention accounts for 27%, while the effective grinding fluid of Comparative Example 1 accounts for only 8%. This is because the present invention performs bionic microstructuring on the surface of the diamond grinding wheel. Due to the surface structural effect, the airflow on the surface of the grinding wheel is uniform, thereby achieving the purpose of improving the utilization rate of the grinding fluid and reducing the loss of the grinding fluid. In addition, the microstructuring of the grinding wheel surface can enhance the chip removal ability, prevent broken abrasive particles and debris from clogging the grinding wheel, and can effectively store the grinding fluid, improve the effective utilization rate of the grinding fluid, thereby reducing the grinding temperature and wear. At the same time, the feather-like grooves can reduce the number of cutting edges in instantaneous contact with the grinding zone, thereby reducing the number of abrasive particles during the scraping process and reducing the grinding force. In addition, compared with Example 2, after the MoS2+TiAlN coating is applied to Example 1 of the present invention, the grinding wheel has the advantages of high hardness, wear resistance, corrosion resistance, high melting point and high thermal conductivity, which improves the hardness, strength, wear resistance and oxidation resistance of the grinding wheel, thereby extending the service life of the grinding wheel and improving the grinding efficiency. This is because the addition of the Al element makes the grinding wheel have the advantages of high hardness, wear resistance, corrosion resistance, high melting point and high thermal conductivity. At high temperature, Al ions will diffuse to the surface and easily form a dense Al2O3 protective film, which improves the hardness, strength, wear resistance and oxidation resistance of the grinding wheel, thereby extending the service life of the grinding wheel and improving the grinding efficiency. The Ti transition layer deposition treatment is first performed on the grinding wheel substrate, which serves to improve the adhesion of the diamond grinding wheel substrate and the molybdenum disulfide coating and improve the quality of the molybdenum disulfide coating. The experimental results of the grinding wheels obtained in Example 2 and Example 3 are close to those in Example 1, and will not be repeated here.

[0076] In summary, the method of the present invention adopts a bionic bird feather structure with leaf sequence arrangement, which can improve the chip removal ability, prevent broken abrasive particles and debris from clogging the grinding wheel, and can effectively store the grinding fluid, improve the effective utilization rate of the grinding fluid, thereby reducing the grinding temperature and wear. At the same time, coated with MoS2+TiAlN coating, the grinding wheel has the advantages of high hardness, wear resistance, corrosion resistance, high melting point and high thermal conductivity, which improves the hardness, strength, wear resistance and oxidation resistance of the grinding wheel, thereby extending the service life of the grinding wheel and improving the grinding efficiency.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite anti-wear coating combined structured grinding wheel, characterized in that: The following steps are involved: Step 1: Performing bionic microstructuring on the surface of the grinding wheel to form a bird-feather-like microstructure in leaf sequence arrangement on the surface of the grinding wheel; The diamond grinding wheel surface is processed by bionic microstructuring using femtosecond laser: First, the bird feather structure is drawn into a pattern according to the leaf sequence; then, the drawn pattern is imported into the laser system, and by setting the laser processing spot size and processing time related parameters, the system scans and ablates the grinding wheel surface along the pattern trace; finally, bird feather grooves arranged according to the leaf sequence are formed; The average power of the laser is 5w, the repetition frequency is 80Mhz, the pulse width is 120fs, the wavelength is 870nm, and the laser spot diameter is within 10um. The bird feather structure is processed along the arc on the surface of the grinding wheel. The number of abrasive clusters in leaf sequence is 330, and the leaf sequence coefficient is 0.4865. The bird feather structure parameters are groove depth of 0.3mm, shaft groove width of 1mm, barb groove width of 0.5mm, distance between two barb grooves of 1.5mm, barb groove angle of 35°, and number of barbs of 6. Step 2: Surface treatment of the grinding wheel substrate of step 1: specifically: first use clean water to clean the diamond grinding wheel to remove most of the impurities on the surface of the substrate; then put the substrate into a sodium hydroxide solution to remove grease on the surface of the substrate; then put the substrate into a nitric acid solution to remove surface oxides; finally, dry the substrate; Step 3: Use a plasma cleaning machine to glow clean the substrate to remove dirt and impurities on the surface of the substrate; then, turn on the DC magnetron power supply to prepare a Ti transition layer on the grinding wheel substrate after surface treatment; Step 4, adopting the dual-target radio frequency magnetron sputtering method, using MoS2 target material and TiAlN target material to apply another layer of MoS2-TiAlN composite anti-wear coating on the surface of the Ti transition layer in step 3: Specifically: First, select suitable MoS2 target material and TiAlN target material; secondly, place the cleaned substrate and target material in an ion plating machine, and evacuate the working room to a vacuum state; then introduce Ar gas and maintain the gas pressure at 5Pa to make the atoms on the target surface more active; finally, use ions to bombard the target material to ionize the atoms on the surface of the MoS2 target material and the TiAlN target material and deposit them on the substrate surface to obtain the composite anti-wear coating combined structured grinding wheel.

2. A composite anti-wear coating combined structured grinding wheel, characterized in that: The grinding wheel is prepared by the preparation method described in claim 1; the grinding wheel comprises a grinding wheel matrix, and the surface of the grinding wheel matrix is ​​provided with a phyllotaxy arranged bird feather-like microstructure; the surface of the grinding wheel matrix is ​​provided with a Ti transition layer and a MoS2-TiAlN composite anti-wear coating in sequence.

Citation Information

Patent Citations

  • Preparation method of diamond grinding wheel micro-nano textured coating

    CN112430796A

  • Structured grinding wheel based on combined bionic thought

    CN114193342A

  • A low friction coating for a cutting tool

    WO1999055930A1